New Urban Landscapes and Urban Image - Zeynep Eraydın (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Recent accounts of place branding seen to have become an important tool for the cities which eagerly demand to take place in the global competition. Within this perspective of creating a brand image, urban space has become the scene for new urban landscapes for making city attractive, yet, the existing urban image and identities of urban places have ignored. This paper intends to highlight this omission by evaluating the brand image which is created through place branding strategies from a perspective of environmental psychology, to reveal the mismatch between inhabitants’ urban image and policy makers’ brand image. Using Ankara as the case study, which has recently put the place branding on the top of urban development agenda, a survey is presented in order to figure out whether the brand image corresponds with the urban image. The findings demonstrate that new urban landscapes designed through branding strategies do not take place in accumulated urban image. Consequently, this paper puts forth inhabitants’ main concerns on urban image and identity which can potentially play a crucial role in developing urban politics.